A study on epidemiological and clinical profile of Acute Pancreatitis in a Tertiary Care Center in Eastern Nepal - Mandal, Rajesh Kumar; Peeyush, Denis; Subedi, Prashant; Tiwari, Pushpendra; Pradhan, Bickram (Journal of Advances in Internal Medicine, 2025)
BACKGROUND Acute pancreatitis is the inflammation of pancreatic parenchyma. It can present as mild to severe disease with diverse local and systemic complications. Alcohol and biliary are the most common etiologies of acute pancreatitis. This study aimed to study the epidemiological and clinical profile of acute pancreatitis including etiology, complications and severity of acute pancreatitisMETHODS The study was a cross sectional study, conducted from May 2021 to April 2024 in the Department of Gastroenterology and Hepatology. Data regarding clinical and epidemiological profiles of patients of acute pancreatitis were entered in Ms Excel and analyzed by SPSS 20.RESULTS The mean age of patients was 45.06 years, age ranging from 15- 84 years with male 94(71.75%) and female 37(28.24%) (M:F=2.54:1). Alcohol 65(49.61%) followed by biliary 22(16.79%) was the common etiology of acute pancreatitis. The most common complication of acute pancreatitis was ascites 34(25.95%) followed by pleural effusion 28(21.37%) and acute fluid collection 24(18.32%). Majority 86(65.64%) was mild and 36(27.48%) had moderate severe and 9(6.87%) had acute severe pancreatitis. Most of the patients had raised CRP levels. 92(70.22%) of patients had CRP between 6-150 mg/dl, 23(17.55%) had CRP > 150 mg/dl. While 16(12.21%) of the patients had normal CRP < 6 mg/dl.CONCLUSIONS Alcohol abuse and gallstones were the most common etiologies of acute Pancreatitis. It was common in males and in middle age groups. Most of the patients presented with mild severity and common sequelae included ascites, pleural effusion and acute fluid collection.